Tissue Culture of a Medicinal Plant-Aloe Vera - Aggarwal, Diwakar (My University, 2007)
Aloe vera syn barbadensis Mill. is an important medicinal plant and used world wide in drug and cosmetic industry. Although Aloe propagates vegetatively in its natural state, but propagation rate is too slow to meet demand of high quality planting material for commercial cultivation. Micropropagation method for elite selection of Aloe vera by axillary branching method using shoot tip as explant was standardized. Shoot cultures were initiated on MS medium containing BA 0.2mg/L with IBA 0.2mg/L. Maximum shoot proliferation was achieved on medium containing BA 1.0mg/L with IBA 0.2 mg/L within 28 days of culture. Shoot proliferation was better in liquid medium with same composition. Citric acid also enhanced shoot proliferation. A maximum of 5-multiplication rate of shoots was achieved with citric acid (10mg/L) in the medium. Hundred percent rooting of microshoots was obtained on phytohormone – free MS medium. Regenerated plants after hardening were transferred to soil and they showed 85% survival. The regenerated plants were morphologically similar to control plants.
Keywords: Aloe Vera; Tissue Culture; Phytohormone; Musambar